3 3 METHOD FOR MANUFACTURING A THREE-DIMENSIONAL POROUS ELECTRODE IN WHICH A THIN PROTECTIVE LAYER IS FORMED THROUGH AN ELECTRODEPOSITION COATING A THREE-DIMENSIONAL POROUS ELECTRODE MANUFACTURED FROM THE METHOD AND A LITHIUM SECONDARY BATTERY CONTAINING THE SAME - LEE DAE HO; KIM BYUNG GON; PARK JUN HO; YOONEUN; LEE SANG MIN; CHOI JEONG HEE; LEE MIN HO (2022)
본 발명은 전착 코팅을 통해 보호막이 형성된 3차원 다공성 전극 구조체의 제조방법, 이로부터 제조되는 3차원 다공성 전극 구조체 및 이를 포함하는 리튬이차전지에 관한 것으로, 더욱 상세하게는 이미드계 고분자를 기반으로 리튬이온 이동성이 향상된 고분자 소재를 제조하고, 이를 하전된 콜로이드 분산액 형태로 제조한 후 전착 코팅을 통하여 복잡한 미세구조의 전극 표면에 균일한 박막형 보호막을 형성시킬 수 있도록 하는 방법에 관한 것이다. 이러한 본 발명은, 제1용매 하에서 디아민계 단량체와 산무수물 단량체를 용해 및 반응시켜 폴리아믹산 수지를 제조하는 단계; 폴리아믹산 수지에 중화제를 혼합하여 폴리아믹산 염을 제조하는 단계; 폴리아믹산 염에 물, 알코올 중 어느 하나 이상의 제2용매를 혼합하여 폴리아믹산 염 콜로이드 분산액을 제조하는 단계; 3차원 다공성 금속기판에 폴리아믹산 염 콜로이드 분산액을 전착 코팅하여, 표면에 이미드계 고분자 보호막이 형성된 전극 구조체를 제조하는 단계;를 포함하는 것을 기술적 요지로 한다. The present invention relates to a method for manufacturing a three-dimensional porous electrode structure having a protective film formed by electrodeposition coating, a three-dimensional porous electrode structure manufactured thereby, and a lithium secondary battery comprising same, and, more specifically, has a technical subject matter comprising the steps of: dissolving a diamine-based monomer and an acid anhydride monomer in a first solvent and reacting same to prepare a polyamic acid resin; mixing a neutralizing agent with the polyamic acid resin to prepare a polyamic acid salt; mixing the polyamic acid salt with a second solvent, which comprises water and/or an alcohol, to prepare a polyamic acid salt colloidal dispersion solution; and electrodeposition-coating the polyamic acid salt colloidal dispersion solution on a three-dimensional porous metal substrate to manufacture an electrode structure having an imide-based polymer protective film formed on the surface thereof.